The divine economy: how religions compete for wealth, power, and people - Seabright, Paul (New Jersey Princeton University Press, 2024)
Religion in the twenty-first century is alive and well across the world, despite its apparent decline in North America and parts of Europe. Vigorous competition between and within religious movements has led to their accumulating great power and wealth. Religions in many traditions have honed their competitive strategies over thousands of years.